2014
DOI: 10.2337/dc14-0779
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Development of Left Ventricular Diastolic Function in Patients With Type 2 Diabetes

Abstract: OBJECTIVELeft ventricular diastolic dysfunction (LVDD) is considered to be common in patients with type 2 diabetes mellitus (T2DM), but information on its progression over time is lacking. We studied the longitudinal development of left ventricular diastolic function (LVDF) and myocardial blood flow reserve in patients with T2DM who were free from clinically detectable cardiovascular disease. RESEARCH DESIGN AND METHODSThe LVDF was assessed in 73 patients with T2DM (mean age 67 6 7 years; males 51%) on two occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This is followed by a late stage, which is characterized by alteration in microvasculature compliance, an increase in LV size, and a decrease in cardiac performance leading to symptomatic HF. Predictors for progression to the late stage, which may take several years, include comorbidities often seen in T2DM such as coronary artery disease, hypertension, overweight/obesity, and microvascular changes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by a late stage, which is characterized by alteration in microvasculature compliance, an increase in LV size, and a decrease in cardiac performance leading to symptomatic HF. Predictors for progression to the late stage, which may take several years, include comorbidities often seen in T2DM such as coronary artery disease, hypertension, overweight/obesity, and microvascular changes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found no independent correlation between alteration of diastolic function and poor glycemic control (19,23). Women seem to be more predisposed than men to develop LVDD (10,15,26). Moreover, in middleaged and elderly Korean patients at risk of developing CAD, the correlation between metabolic syndrome components and LVDD was more pronounced in women than in men, suggesting a possible role of sex hormones in metabolic syndrome associated LV diastolic function alterations (30).…”
Section: Epidemiologic and Clinical Aspectsmentioning
confidence: 95%
“…When patients had both diabetes and HT, a higher LV end-diastolic pressure was found compared with either condition alone, suggesting an additional risk for the occurrence of LVDD in these patients compared to those with HT alone (25). Nevertheless, in patients without concomitant disease such as HT and CAD, followed up for 6 years, the authors reported that the prevalence of LVDD was relatively low, suggesting that in the early stage of LVDD, there may be a slow progression of myocardial changes (26). Duration of diabetes, age and abnormally elevated levels of Hb1AC were independently correlated with LVDD in several studies (15,21,27,28,29).…”
Section: Epidemiologic and Clinical Aspectsmentioning
confidence: 97%
“…Cardiomyocyte apoptosis and myocardial fibrosis are the early major pathological changes of DCM. Although the exact prevalence of DCM is unknown, the incidence of diastolic dysfunction in patients with T2DM is up to 30% in some studies . Accumulating evidence suggests that left ventricular diastolic dysfunction (LVDD) is the earliest clinical manifestation of DCM, and LVDD implies cardiac tissue remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact prevalence of DCM is unknown, the incidence of diastolic dysfunction in patients with T2DM is up to 30% in some studies. 5 Accumulating evidence suggests that left ventricular diastolic dysfunction (LVDD) is the earliest clinical manifestation of DCM, and LVDD implies cardiac tissue remodeling. Poirier and his colleagues found that about 60% of T2DM patients without hypertension and cardiovascular diseases were found with LVDD by cardiac tissue Doppler.…”
Section: Introductionmentioning
confidence: 99%